Visible persons, invisible work? Exploring articulation work in the implementation of person-centred care on a hospital ward (Sociologisk Forskning, 2017)
Visible persons, invisible work? Exploring articulation work in the implementation of person-centred care on a hospital wardRecently, many initiatives promoting a holistic view of the patient have been developed. In the last 20 years, different models and frameworks have been advanced to operationalize these different forms of holistic care. This article focuses on one specific case of holistic person-centred care, using the sociological theories of articulation work and invisible work to investigate the efforts involved in sustaining its realization. The article builds on a small ethnographic study conducted at a ward in a Swedish hospital implementing person-centred care. Following a nurse, and her patient, through a ‘person-centred’ admission process and its subsequent procedures, it is argued that person-centred care depends on nurses performing many new tasks which are rarely recognized and appreciated. Secondly, it is argued that nurses are continually asked to do what Anselm Strauss defined as articulation work, coordinating between these different new tasks and established duties. Thirdly, the article discusses the tensions arising when implementing a formalized model of care, which builds on a critique of standardization and objectification, and the work that is excluded and invisible in such routinized operationalization. Finally, it is concluded that while the successful implementation of person-centred care is often argued to rely on the willingness of nurses to surrender old habits, it seems rather to hinge on the skilled inventiveness of these nurses and their ability to overcome the practical difficulties they encounter.